1990
DOI: 10.1177/036354659001800302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the glenoid labrum

Abstract: Shoulder complaints are common in the athletic population. Successful treatment is dependent upon the ability to correctly identify the pathologic changes associated with a specific disorder and arrive at an accurate diagnosis. Labral abnormalities are traditionally associated with glenohumeral instability. Isolated labral tears or degenerative changes may also cause shoulder dysfunction. A reliable clinical tool to assess the status of the labrum would be useful for diagnosis and management of shoulder disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Identification of these findings was generally not significantly different whether 3D or 2D GRE imaging was used. Although they were not objective criteria indicating definite GLC pathology in our study, these findings have proven to be helpful in corroborating the diagnosis of labral injury [11][12][13].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Identification of these findings was generally not significantly different whether 3D or 2D GRE imaging was used. Although they were not objective criteria indicating definite GLC pathology in our study, these findings have proven to be helpful in corroborating the diagnosis of labral injury [11][12][13].…”
Section: Discussionmentioning
confidence: 57%
“…An advantage of MRI is that the GLC can also be evaluated. The standard MRI survey of the GLC usually employs 2D imaging with axial gradient-echo or T2-weighted sequences [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the glenoid labrum, the sensitivities, specificities, and accuracies noted for MRI studies of surgically confirmed glenoid labral tears has varied widely in the literature (59-88%, 58-100%, 33-87%, respectively). 1,3,4,[7][8][9][10]15,17,18,24,29,31 The addition of contrast in MR evaluation of these injuries has traditionally slightly improved the accuracies in these studies (79-89%). We evaluated sensitivities, specificities, and accuracies for superior, anterior, and posterior labral tears, and found that the accuracies of the radiologists in our community setting were consistent with historical values cited.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Sensitivities and specificities have been reported at greater than 90% in certain studies in detecting unidirectional tears of the glenoid labrum on noncontrast MRI, and even higher values have been reported with MR arthrography. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Little has been written, however, regarding the use and accuracy of MRI in identifying labral tears involving more than 1 location of the glenoid. 1,4 The purpose of this study was to evaluate the sensitivity of preoperative MRI, including both noncontrast MRI and MR arthrography, in detecting combined lesions of the anterior, posterior, and superior glenoid labrum.…”
mentioning
confidence: 99%